If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(d + 5) + 2d = 0 Reorder the terms: 3(5 + d) + 2d = 0 (5 * 3 + d * 3) + 2d = 0 (15 + 3d) + 2d = 0 Combine like terms: 3d + 2d = 5d 15 + 5d = 0 Solving 15 + 5d = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 5d = 0 + -15 Combine like terms: 15 + -15 = 0 0 + 5d = 0 + -15 5d = 0 + -15 Combine like terms: 0 + -15 = -15 5d = -15 Divide each side by '5'. d = -3 Simplifying d = -3
| 4x+67y-93x-4y=3x+y-9x | | -2=I+11 | | 8z^2+18z+9= | | 7+3r-3=9r+5-5r | | 5x+12x=85 | | 3.7r-2.2=-3.6+3.9r | | 16x^2-16x+3= | | 15=3(y-3)+y | | F-8=6 | | 5-(9-6x)=0.2x+1.8 | | 12=-6x+3x | | 2x(x-2)=0 | | W-2=-14 | | 9x=-13+y | | 3x^2+33=18 | | 6x^2-53-9=0 | | 7y-7x=3 | | 0=b-2+b | | 3x-4(5x-6)=17-8x | | 1+2n-6=3 | | 4n+5n=0 | | 6.7p-5.8=-6.1+6.6p | | b+3(b+2)=5 | | -5y+3=-4(2y+6) | | M=-9 | | 5+11t-2=6t+48-4t | | 6.7p-5.8=-6+6.6p | | 4(5x+9)=-37+33 | | 4(8-m)=56 | | 6.7p+5.8=-6+6.6p | | 2(5x+5)=-43+33 | | 5(a+3)-a=23 |